Spatial Inequality of Industrial Human Resources: A Composite LDGS Approach - Rusdy Setiawan; Irawati HM; Djuanda Hatta (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study analyzes the spatial dynamics of industrial human resources in North Kalimantan Province. Using secondary data (2011–2022), it applies a Composite LDGS Index integrating Location Quotient, Dynamic LQ, Growth Rate Model, and Shift Share, complemented by Klassen Typology and Moran’s I–LISA spatial analysis. The findings reveal polarized industrial labor distribution, with Tarakan and Bulungan forming a high–high growth cluster, while Malinau and Tana Tidung remain low–low lagging regions. The results confirm that regional competitiveness and specialization dynamics, rather than growth alone, drive spatial inequality in industrial human resource development. Furthermore, infrastructure disparities, uneven investment flows, and differences in human capital quality contribute to the persistence of regional gaps. The study suggests that targeted regional policies, improved inter-district connectivity, and capacity-building programs are essential to reduce spatial inequality. Strengthening industrial linkages and promoting equitable development strategies are also crucial to enhance balanced growth across North Kalimantan Province and support long-term sustainable regional development outcomes.